DEVELOPMENT OF ENVIRONMENT ON CLEAN AND HEALTHY LIVING LEARNING-BASED TEACHING MATERIAL - Sepita Ferazona; Suryanti; Nilam Cahaya; Melqi Okta Kisti; Leni Maryani (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This paper is developmental research, which aims to produce environmental-based teaching materials on valid clean and healthy living environment learning material. The developmental research uses the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation. The data collection instrument used was a validated validation sheet. The data were obtained by validating the validation from material, media, and learning experts on the modules developed by conducting limited validity trials. Data analysis was analyzed through the quantitative description. The validation results of the material expert indicate that the developed teaching materials were very valid with an average percentage of 96%. The media expert validation results show that the developed teaching materials were very valid with an average percentage of 100%. The validation results of learning experts imply that the developed teaching materials were very valid with an average percentage of 100%. Based on the experts’ validation results, an environment of clean and healthy living material-based module product was obtained with a very valid category used in learning.